Critical criminology and the struggle against climate change ecocide - White, R. D. (Critical criminology, 2015)
This article provides an outline for action against climate change ecocide. Critical criminology has primarily focussed on exposing the political economy surrounding global warming and the powerful interests that perpetuate harmful practices even in the light of overwhelming scientific evidence. Questions of activist intervention have been less forthcoming, although specific attention has been given to concepts such as ecocide to highlight the criminality and social and ecological injustices involved in "business as usual." After discussing the nature and dynamics of the nation-state and global capitalism, the article then presents an action plan matrix that incorporates elements relating to law and legal reform, environmental law enforcement, courts and adjudication, and social action. The article argues for the necessity of greater integration of theory and practice through the development of a social praxis for climate change justice.